2017
DOI: 10.1016/j.rmed.2017.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targets in idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and ultimately fatal interstitial lung disease. After many drugs failed in clinical trials, improvements in the understanding of the pathogenesis of IPF led to the approval of two drugs that slow the progression of the disease. However, the prognosis for patients with IPF remains poor and the search continues for drugs that inhibit the pathogenic pathways active in IPF to reduce or even halt the progression of the disease. In this article, we review the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 71 publications
2
78
0
1
Order By: Relevance
“…Alternatively, our findings in this study and in [18] provide rationale for the use of GPCR agonists of G αs -coupled receptors as treatments that actively trigger YAP/TAZ inactivation and thus will have an antifibrotic potential. This is supported by reports that activating IP receptor by selexipag, treprostinil and iloprost [18,[83][84][85][86][87][88][89], β2-adrenoreceptors by oladaterol [90], or melatonin receptors by melatonin [91] is antifibrotic in vitro and in animal fibrosis models, and at the same time inhibits YAP/TAZ [18,23,91].…”
Section: Discussionsupporting
confidence: 55%
“…Alternatively, our findings in this study and in [18] provide rationale for the use of GPCR agonists of G αs -coupled receptors as treatments that actively trigger YAP/TAZ inactivation and thus will have an antifibrotic potential. This is supported by reports that activating IP receptor by selexipag, treprostinil and iloprost [18,[83][84][85][86][87][88][89], β2-adrenoreceptors by oladaterol [90], or melatonin receptors by melatonin [91] is antifibrotic in vitro and in animal fibrosis models, and at the same time inhibits YAP/TAZ [18,23,91].…”
Section: Discussionsupporting
confidence: 55%
“…Pirfenidone (5-methyl-1-phenyl-2-[1H]-pyridone), a bioavailable synthetic molecule, is the first drug to be approved for use on IPF patients. It is an anti-inflammatory and anti-fibrotic agent that down-regulates transforming growth factor beta (TGF-β) and tumor necrosis factor alpha (TNF-α), inhibits collagen synthesis and reduce fibroblast proliferation [7,8]. Two largest randomized clinical trials for pirfenidone on IPF patients, the CAPACITY and ASCEND trials, demonstrated a slower decline of the lung function and sufficient drug tolerability [9,10].…”
mentioning
confidence: 99%
“…This contrasts with other conditions, notably idiopathic pulmonary fibrosis which have experienced a similar renaissance but where positive phase 3 trials have led to the licensing of new drugs and a positive impact on patients outcomes. 11 The repeated failure of trials in bronchiectasis to give positive outcomes necessitates a re-evaluation of our approach 10,[11][12][13][14][15] In this review, we outline novel approaches to the management of bronchiectasis in adults aiming to take us beyond antibiotics and beyond the recommended therapies in recent guidelines. 4 Furthermore, we propose that recent randomized trials have struggled to show clinical benefits because of the unresolved heterogeneity of bronchiectasis, and that a more logical, stratified approach to therapy will be required going forward.…”
Section: Introductionmentioning
confidence: 99%